Halogen regulation of inorganic perovskites toward robust triboelectric nanogenerators and charging polarity series. Issue 28 (13th July 2020) - Yu, Xueping; Wang, Yudi; Zhang, Jihua; Duan, Jialong; Yang, Xiya; Liu, Liming; Tang, Qunwei
Abstract : CsPbX3 (X = Cl −, Br −, I − ) halide perovskites are investigated focusing on their triboelectric charging behaviors. A modified series containing inorganic perovskites is established with the order of CsPbBr3, CsPbI2 Br, and CsPbCl3 from negative to positive. Abstract : Triboelectric nanogenerators (TENGs) are preferred energy conversion devices to scavenge low-frequency mechanical energy sources from ambient environments due to their easy-to-operate principle structures, cost-effectiveness, and wide application areas. Halide perovskites have been demonstrated to be a good candidate as triboelectrification dielectric materials in TENGs, yet their triboelectrification behavior and charging affinity are still unclear. Herein, inorganic CsPbBr3 perovskites doped with halide ions (I − and Cl − ) are systematically investigated focusing on their triboelectric behaviors through fabricating perovskite TENGs in vertical contact-separation mode. The charging polarities of different halide perovskites are qualified and ascertained by evaluating their triboelectric output signals, power density, charging capacity, and figure of merit (FOM), which are confirmed by the deviation of electron binding energy, carrier mobility, surface potential and dielectric properties affected by different halide ion incorporation. Meanwhile, the champion perovskite TENG demonstrates an excellent operational durability in an ambient atmosphere. A modified triboelectric series containing inorganic perovskites with various halide ions is established based on the empirical results. This work not only enriches the triboelectric series, but also expands the application of perovskite materials in mechanical energy harvesting fields.